Hollow mesoporous silica nanoparticles fabrication for anticancer drug delivery - Nguyen Thi, Ngoc Tram; Nguyen, Dai Hai (Vietnam Journal of Science and Technology, 2020)
Mesoporous silica nanoparticles (MSNs) have attracted significant attention from researchers thanks to their high surface area and pore volume, which can increase drug loading capacity. Moreover, MSNs, with their biocompatibility and ease of surface functionalization, are seen as potential drug delivery system. However, the loading of drug into MSNs system still needs further improvement. In this study, hollow mesoporous silica nanoparticles (HMSNs) were fabricated in order to increase the drug loading capacity of nanosilica materials. The synthesized HMSNs possessed inner hollow cores that could remarkably raise the total pore volume and thus improve the capacity for cargo loading. HMSNs were synthesized according to the hard-template method with three main steps: (1) forming of solid SiO2 nanoparticles as templates, (2) forming of core-shell structure by coating MSN layers onto the templates, and (3) forming of hollow core structure by etching away the solid template. The HMSNs product was characterized by TEM, XRD, TGA and FTIR. In addition, drug loading capacity of the material was evaluated with doxorubicin as model drug. The results indicated remarkable improvement in drug loading capacity, compared to MSN sample. Cell assays on cancer lines showed high biocompatibility. These results demonstrated the potential of HMSNs in the delivery of anticancer agents.